إشكالية حديث «حدثوا عن بني إسرائيل ولا حرج» وحلولها في ضوء الدراسات في نقد المتون والإسناد: The problem of the hadith “Transmit from the Children of Israel and there is nothing wrong with it” and its solutions in the light of studies in sanad and matn criticism - Toure Mohamed Abdoul Bassiti ,; Khairil Husaini Bin Jamil, (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث يعتبر حديث «حدثوا عن بني إسرائيل ولا حرج» من الأحاديث المشكلة، لما أثير حوله من إشكالات في السياقات التاريخية والمعاصرة. وقد استخدم هذا المبحث دليلاً من قبل الأفراد الذين يجادلون بأن أصحاب رسول الله ﷺ اعتمدوا كثيرا على تعاليم أهل الكتاب، متأولين الأوامر والنواهي التي نص عليها رسول الله ﷺ فيما يتعلق ببني إسرائيل وأخبارهم ومروياتهم. فيأتي هذا البحث للنظر في ثبوت هذا الحديث معتمدًا القواعد والضوابط المعتبرة في دراسة أسانيد هذه الرواية. ولِما زعم البعض أيضا بأن الحديث مخالف لأحاديث أخرى نحو حديث «لا تسألوا أهل الكتاب عن شيء»، وأن دلالته مخالفة كذلك دلالة آيات في القرآن تحذر المسلمين من اليهود والنصارى وهم المقصود ببني إسرائيل. توصل البحث إلى كون الحديث صحيحًا من جهة أسانيده ومقبولاً من جهة متونه ومعانيه. فحاول البحث دراسة القضايا المثارة حول هذا الحديث وإبراز الردود المقدمة لمعالجة هذه الإشكالات، وتوصل كذلك إلى إمكانية إزالة إشكالية الحديث بالجمع سواء بينه وبين أحاديث أخرى، أو بينه وبين دلالة الآيات المتهمة بمعارضته، أو بنسخ حديث «حدثوا عن بني إسرائيل ولا حرج» مرويات حديث «لا تسألوا أهل الكتاب عن شيء». ABSTRACT The hadith: “Transmit from the Children of Israel and there is nothing wrong with it” is considered one of the problematic hadiths, due to the problems raised around it in the historical and contemporary contexts This hadith has been used as evidence by those who contend that the Companions of the Messenger of God relied heavily on the teachings of the People of the Book, ignoring the prohibitions and commands that the Messenger of God stipulated regarding the Children of Israel and their news and narrations. This study evaluates the authenticity of this hadith based on the principles of hadith criticism. Some further stated that the hadith contradicts other hadiths such as the hadith “Do not ask the People of the Book about anything,” and that its meaning contradicts verses in the Qur’an that warn Muslims against Jews and Christians, who are meant by the term Children of Israel. The research attempted to study the issues raised around this hadith and highlight the responses provided to address these problems. It also reached the possibility of removing the problem of the hadith by combining it with other hadiths, or between it and the meaning of the verses accused of contradicting it, or by abrogating the hadith “Talk about the children of Israel and there is no harm” Hadith narrations “Do not ask the People of the Book about anything”.